2011
DOI: 10.1097/ta.0b013e318216f754
|View full text |Cite
|
Sign up to set email alerts
|

Postinjury Vagal Nerve Stimulation Protects Against Intestinal Epithelial Barrier Breakdown

Abstract: Background Vagal nerve stimulation (VNS) can have a marked anti-inflammatory effect. We have previously shown that preinjury VNS prevented intestinal barrier breakdown and preserved epithelial tight junction protein expression. However, a pretreatment model has little clinical relevance for the care of the trauma patient. Therefore, we postulated that VNS conducted postinjury would also have a similar protective effect on maintaining gut epithelial barrier integrity. Methods Male balb/c mice were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 19 publications
(23 reference statements)
1
40
0
Order By: Relevance
“…Breakdown of the gut barrier is associated with increases in systemic inflammation, distant organ injury, and death [4,6,7,14,20]. Studies have shown that modulation of intestinal epithelial tight junction proteins, through VNS, may be a potential strategy for attenuating gut barrier failure after injury [5,6,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breakdown of the gut barrier is associated with increases in systemic inflammation, distant organ injury, and death [4,6,7,14,20]. Studies have shown that modulation of intestinal epithelial tight junction proteins, through VNS, may be a potential strategy for attenuating gut barrier failure after injury [5,6,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown similar correlations between intestinal permeability and tight junction breakdown in vivo. In a murine model of traumatic brain injury (TBI) [20] or severe burn injury [6,7,14], Enteric Glia Protect the Intestinal Barrier PLOS ONE | www.plosone.orgincreases in intestinal barrier failure, as evidenced by increased paracellular permeability and histologic gut injury, were associated with decreased expression or altered localization of both occludin and ZO-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaky gut syndrome is leading to the translocation of microbial products in the systemic circulation further aggravating the prognostic outcome 87. In several experimental settings, mimicking the loss of intestinal barrier activation of the cholinergic anti-inflammatory pathway has been reported to efficiently reduce both systemic inflammation, to limit loss of barrier function, and to reduce intestinal damage 88 89. Interestingly, as described above, enteral feeding with high-fat diet resulted in the activation of the cholinergic anti-inflammatory pathway reducing systemic inflammation and supporting gut barrier function in a rat model of haemorrhagic shock 21.…”
Section: Other Gi Disordersmentioning
confidence: 99%
“…10,11 The ultimate target of protection is tight junction protein expression in epithelial cells and preservation of their function in the intestinal mucosal barrier.…”
mentioning
confidence: 99%